Bioethanol Production from Starch- A Short Review - G. Veeramani (Journal of Global Pharma Technology, 2019)
Bioethanol is an alcohol made by fermentation, mostly from carbohydrates produced in sugar or starch crops such as corn or sugarcane. Cellulosic biomass, derived from non-food sources, such as trees and grasses, is also being developed as a feedstock for ethanol production. Concentrated acid hydrolysis, dilute acid hydrolysis, wet milling process, dry milling process, sugar fermentation and fractional distillation process were used for production of bioethanol. Bioethanol is colourless and clear liquid. Brazil and United States of America are the largest ethanol producers, widely used alternative automotive fuel consists lower toxicity level. India produced 111 crore liters of ethanol in year 2015-2016, while the production was 38 crore liters in 2013-2014. Bioethanol fuel is mainly produced by the sugar or cellulosic fermentation process and it is transport fuel to replace gasoline and power generation by thermal combustion, fuel for fuel cells by thermochemical reaction, fuel in cogeneration systems and feedstock in the chemical industries because it is much more environmental friendly.Keywords: Bioethanol, Starch, Fuel, Hydrolysis, Hexoses, Fermentation.